Smoking behavior among adolescents in rural schools in Malacca, Malaysia - a case-control study - Mohd Zulkefli, Nor Afiah; Mohd Amin, Rahmah; Md Said, Salmiah; Munn, Sann Lye; Shah, Shamsul Azhar; Idris, Fazilah (Universiti Putra Malaysia Press, 2015)
Smoking among rural adolescents in Malaysia is on the rise with a significant difference seen between urban and rural youths. Therefore, this study was carried out to determine a predictive model of smoking among the rural-school adolescents population in Malacca, Malaysia. An unmatched case-control study was conducted in 2010 involving 484 cases and 444 controls of Form Two students in Malacca, Malaysia, using cluster sampling. Smoking was the dependent factor of this study while the independent factors were individual, family, school and environment. Data were obtained through a self-administered questionnaire. The response rate of the study was 100% whereas the smoking prevalence was 20.9%. Binary logistic regression was used to determine the smoking predictive model. Strong predictors of smoking behavior were: influenced by artistes who smoke (Adjusted OR=8.67, 95% CI 5.53-13.58); the male gender (Adjusted OR=6.7, 95% CI 4.14-10.83); Muslim (Adjusted OR=4.46, 95% CI 2.36-8.44); and the belief that smoking is not dangerous when the teacher is seen smoking as well (Adjusted OR=3.95, 95% CI 2.19-7.10). Other predictors were: being offered cigarettes by friends (Adjusted OR=2.81, 95% CI 1.79-4.42); the belief that smoking will relax the mind (Adjusted OR=2.45, 95% CI 1.33-4.51); having friends who smoke (Adjusted OR=2.32, 95% CI 1.29-4.81); forced by friends to smoke (Adjusted OR=2.17, 95% CI 1.15-4.12); have heard of the national No-Smoking Campaign (Adjusted OR=1.89, 95% CI 1.06-3.37); have problems with the school management (Adjusted OR=1.75, 95% CI 1.07- 2.88); parental consent to watch sexual activities, drug use or violence on television or at the cinema (Adjusted OR=1.73, 95% CI 1.06-2.83); and have lunch in school (Adjusted OR=1.58, 95% CI 1.04- 2.41). This paper ends with the recognition of the need for intervention in dismantling the predictors that can lead to the development of smoking among Malaysian adolescents in rural schools.